The Question of E = mc2 and Rectification of Einsteinas General Relativity (Global Journal of Science Frontier Research, 2014)
The formula E = mc 2 is a speculation that was confirmed by Nuclear fission and fusion, but is not valid for the electromagnetic energy alone because the electromagnetic energy-stress tensor is traceless. On the other hand, for the light rays satisfying E = mc 2 necessitates the existence of a photonic tensor with an anti-gravity coupling added to the Einstein equation with the source of an electromagnetic wave. This is consistent with the massive dynamic case that the Einstein equation must be rectified to the Lorentz-Levi-Einstein equation. Moreover, because the couplings in the Einstein equation must have different signs for the dynamic case that involves gravitational waves, the space-time singularity theorems of Hawking and Penrose actually are irrelevant to physics. The misinterpretation of E = mc 2 as generally valid, is responsible for overlooking the charge-mass interaction, which is crucial for the unification of gravitation and electromagnetism. General validity of E = mc 2 is also in disagreement with experiments. It is pointed out that the interpretations of E = mc^2 of both Nobel Laureates, 't Hooft and Wilczek, just like many others, are also incorrect.
Keywords: einstein’s equivalence principle; dynamic solution; gravitational wave; E = mc2